On a Gauss-Kummer Convergence Model. (27th July 2022) - Bucur, Ileana
Abstract: In Ref. [1], we have given a convergence criterion that generalizes the Gauss criterion for series with positive terms. Now we study the summability of so called "periodically decreasing functions". The main results concern the fact that some compactness assumptions on an "initial time interval" are preserved on the entirely time semi-axis.